Plant communities of trampled habitats in North Korea - Mucina, Ladislav; Dostalek, J.; Jarolimek, I.; Kolbek, J.; Ostry, I. (1991)
A syntaxonomic study of trampled plant communities in North Korea is presented. Analytic and synthetic methods of the Braun-Blanquet approach together with a numericsyntaxonomical analysis (cluster analysis and principal coordinate analysis ordination) were employed. With the exception of the Bryo-Saginetum japonicae, all the associations, such as the Artemisio asiaticae-Plantaginetum asiaticae, Plantagini depressae-Polygonetum avicularis, Polygonoavicularis-Potentilletum costatae, Eragrostio multicaulis-Plantaginetum depressae, Euphorbio maculatae-Centipedetum minimae, Digitario ectiniformis-Eleusinetum indicae and Setario viridis-Chlorisetum virgatae, are described for the first time. Some communities also include a number ofsubassociations. Trampled communities are found along edges of paths and in cracks among paving stones. Soils vary from loamy to sandy and skeletal. A phenomenon of seasonality in expression of ruderal communities was observed in North Korea. It is assumed that this seasonality is controlled by pattern of precipitation showing distinct climatic seasons (e.g. pre-monsoon and postmonsoon periods). The ruderal vegetation seasonality is supposed to become more pronounced towards tropical regions. Several mesophilous or slightly hygrophilous European species occur frequently in North Korean trampled communitiesincluding Chenopodium glaucum, C. ficifolium and Potentilla supina. Their occurrence in trampled habitats is hypothesized as being related to high air humidity and associated wet climate.